SYNTHESIS AND APPLICATION OF HIGH-QUALITY CARBON NANOFIBERS TO INCREASE THE PERFORMANCE OF AIRCRAFT PARTS - H. R. Shahverdi; H. M. Boer (Научный вестник МГТУ ГА, 2017)
Modern carbon nanofibers (CNF), obtained from polyacrylonitrile (PAN), do not have high tensile strength. It is because there is still no understanding how the electroforming method affects the quality of CNF.This paper investigates a process to obtain high-strength nanofibers with a carbon content of up to 90% by the method of electroforming. The research made it possible to obtain CNFs with a diameter of 150-500 nm with uniqueproperties due to our CNF continuous and combined forms, which distinguishes our CNFs from existing ones when appliedto composite materials. Such nanofibers, obtained by selecting the optimum stabilization temperature and carbonization regime, have homogeneous cross sections, and as a result of improving their mechanical properties, the aircraft structure performance can be substantially improved.